2018
DOI: 10.1108/ijmf-10-2017-0235
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear approach to Random Walk Test in selected African countries

Abstract: Purpose-The purpose of this paper is to reexamine the weak form efficiency of five African stock markets (South Africa, Nigeria, Egypt, Ghana and Mauritius) using various tests to assess the impact of non-linearity effect and thin trading which are prevalent in African markets on market efficiency. Design/methodology/approach-The weekly returns of S&P/IFC return indices for five African countries over the period 2000-2013 were obtained from DataStream and analyzed. The study adopted the newly developed Non-Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
1
14
0
1
Order By: Relevance
“…In general the obtained results are hybrid, since we have total and partial rejections of the random walk hypothesis and the information efficiency hypothesis. These results are in accordance with evidence obtained by other researchers, namely with the studies of Richards (1997), Worthington and Higgs (2013), Dsouza and Mallikarjunappa (2015), Hamid et al (2017), Aggarwal (2018), Sadat and Hasan (2019) and, partially, with those of Ngene et al (2017), Abakah et al (2018) and Malafeyev et al (2019).…”
Section: Methodssupporting
confidence: 93%
“…In general the obtained results are hybrid, since we have total and partial rejections of the random walk hypothesis and the information efficiency hypothesis. These results are in accordance with evidence obtained by other researchers, namely with the studies of Richards (1997), Worthington and Higgs (2013), Dsouza and Mallikarjunappa (2015), Hamid et al (2017), Aggarwal (2018), Sadat and Hasan (2019) and, partially, with those of Ngene et al (2017), Abakah et al (2018) and Malafeyev et al (2019).…”
Section: Methodssupporting
confidence: 93%
“…Gimba, McKerrow, N'Dri, Abakah, Alagidede, Mensah and Ohene-Asare [54][55][56][57], tested the chances of random walk hypothesis in African markets. Gimba [54] studied the Nigerian Stock Exchange (NSE), analyzed daily data from January 2007 to December 2009, and weekly data from June 2005 to December 2009.…”
Section: The Efficient Market Hypothesis In Its Weak Formmentioning
confidence: 99%
“…The results suggest that random walk hypothesis cannot be rejected, evidencing that BRVM markets are efficient in its weak form. Abakah, Alagidede, Mensah e Ohene-Asare [57] examined the markets of South Africa, Nigeria, Egypt, Ghana and Mauritius during the period 2000-2013. The authors suggest mixed results, arguing that used methodology may indicate different results.…”
Section: The Efficient Market Hypothesis In Its Weak Formmentioning
confidence: 99%
“…Similarly, in Africa, empirical studies conducted remain inconclusive yielding weak-form efficient (Adigwe et al, 2017;Bulla, 2015;Bundoo, 2000;Simons and Laryea, 2005; Van et al, 2013), inefficient (Awiagah and Choi, 2018;Ayentimi et al, 2013;Chikoko and Muparuri, 2013;Katabi and Raphael, 2018;Lawal et al, 2017;Nwidobie, 2014;Smith, 2008;Zaman, 2019), mixed results (Abakah, et al, 2018;Phiri, 2015;Vitali and Mollah; and strong-form efficient (Kelikume, 2016) (see Table 1, Appendix-I).…”
Section: Empirical Literaturementioning
confidence: 99%
“…Empirical studies conducted for Africa remain inconclusive with mixed reports. This contrary reports are evident in the works (Adigwe, Ugbomhe and Alajekwu, 2017;Bulla, 2015;Bundoo, 2000;Simons and Laryea, 2005; Van et al, 2013) which supported weak-form efficient market hypothesis, but many studies documented inefficient market hypothesis (Awiagah and Choi, 2018;Ayentimi, Mensah and Naa-Idar, 2013;Chikoko and Muparuri, 2013;Katabi and Raphael, 2018;Lawal, Somoye and Babajide, 2017;Nwidobie, 2014;Smith, 2008;Zaman, 2019); while few studies reported mixed results (Abakah et al, 2018;Phiri, 2015;Vitali and Mollah, 2015). Additionally, Kelikume (2016) recorded strong-form efficient market hypothesis.…”
mentioning
confidence: 91%